2020
DOI: 10.1038/s41419-020-02864-5
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of cyclophilin D at serine 191 regulates mitochondrial permeability transition pore opening and cell death after ischemia-reperfusion

Abstract: The mitochondrial permeability transition pore (mPTP) plays a critical role in the pathogenesis of cardiovascular diseases, including ischemia/reperfusion injury. Although the pore structure is still unresolved, the mechanism through which cyclophilin D (CypD) regulates mPTP opening is the subject of intensive studies. While post-translational modifications of CypD have been shown to modulate pore opening, specific phosphorylation sites of CypD have not yet been identified. We hypothesized here that phosphoryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 59 publications
0
27
1
Order By: Relevance
“…However, this has not been the end of the story, as the post-translational regulation of mPTP by phosphorylation and S-acylation of CsA is receiving special attention. Preventing CypD phosphorylation at S191 by inhibiting the glycogen synthase kinase-3β (GSK3β) reduces the translocation and binding of CypD to OSCP, avoiding increased ROS production, mPTP opening and subsequent cell death at reperfusion [234]. Moreover, it has been demonstrated that C202 in CypD is S-acylated and that ischemia induces deacylation and Ca 2+ overload.…”
Section: Pyroptosismentioning
confidence: 99%
“…However, this has not been the end of the story, as the post-translational regulation of mPTP by phosphorylation and S-acylation of CsA is receiving special attention. Preventing CypD phosphorylation at S191 by inhibiting the glycogen synthase kinase-3β (GSK3β) reduces the translocation and binding of CypD to OSCP, avoiding increased ROS production, mPTP opening and subsequent cell death at reperfusion [234]. Moreover, it has been demonstrated that C202 in CypD is S-acylated and that ischemia induces deacylation and Ca 2+ overload.…”
Section: Pyroptosismentioning
confidence: 99%
“…A regulatory role of Cyp-D to mPTP-opening was first suggested by the inhibitory effect of cyclosporin A (Cs-A) on Ca 2+ -induced mPTP opening and by the subsequent discovery that Cs-A binds to Cyp-D [ 32 , 33 ]. It has recently been reported that the mPTP sensitizing effect of Cyp-D is potentiated by the phosphorylation of Cyp-D at Ser191 [ 34 ]. It would be of importance to identify responsible kinases for this phosphorylation ( Figure 2 B).…”
Section: Mitochondrial Death Pathwaymentioning
confidence: 99%
“…Opening of the pore depolarizes the mitochondrial membrane and initiates cell death [ 39 ]. Kinases can mitigate pore opening and reduce the detrimental effects of oxidative stress by activating cell survival pathways [ 40 , 41 ]. These studies implicate a crucial role for kinases in I/R injury and cardioprotection.…”
Section: Myocardial Ischemia–reperfusion Injurymentioning
confidence: 99%